The art of failure in translating a Navajo poem - Anthony K. Webster (Journal de la Société des Américanistes)
This article engages John Ciardi’s famous dictum that translation is « the art of failure » by engaging in a thick translation and a creative transposition of a short poem in Navajo by Rex Lee Jim. I begin with reflections on recent discussions in anthropology on translation and voice – both of which will be relevant to the argument advanced in my discussion of Jim’s poem. I then work through a transcript of an interview with Jim about his poetry. I then engage in a creative transposition, or more precisely a failure, of the poem, and engage in a bit of exegesis and philology about the poem. The goal is to bring a concern with voice into dialogue with a concern with theorizations of translation. Mostly, though, this article is a contemplative exercise in the art of failure and in attending to the value of such an intellectual and aesthetic endeavor.